Pengaruh Kualitas Produk, Gaya Hidup, dan Citra Merek Terhadap Minat Beli iPhone di Kalangan Mahasiswa (IJM: Journal of Multidisiplinary, 2025)
Apple launched the iPhone, a smartphone brand with a high level of purchase demand, especially among younger consumers. Nevertheless, iPhone devices have failed to establish themselves as market leaders around the world. Therefore, the purpose of this research is to ascertain how brand image, lifestyle, and product quality affect students' interest in buying an iPhone. The research population consisted of management students of Bhayangkara University, Greater Jakarta. 108 samples were collected using the hair formula and purposive sampling technique. SPSS version 30 was used to process the data for this study, which used a multiple linear regression analysis strategy. The results of this study show that there is an interaction between variables that affect each other as described below: 1) Partially product quality has a significant effect on buying interest. 2) Lifestyle has a positive and significant effect on buying interest. 3) Brand Image has a positive and significant effect on buying interest. 4) Partially, product quality, lifestyle and brand image have a positive and significant effect on buying interest.